2007
DOI: 10.22230/cjc.2007v32n3a1853
|View full text |Cite
|
Sign up to set email alerts
|

Fit to Print: A Natural History of Obesity Research in the Canadian News Media

Abstract: This natural-history approach to investigating media reports concerning health can reveal the complex process whereby health research becomes news. Using television and newspaper reports of a press event taken from a larger project, this article examines the inception and mediation of obesity research in the Canadian news media. By exploring questionnaire data, a media release, telephone interviews with journalists, and news reports, we can better understand the meaning making that occurs at all levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…This finding contrasts with Iyengar's research, in which episodic framing dominated news coverage of social ills. Roy, Faulkner, and Finlay (2007) and Sandberg (2007) identified similar framing patterns in Canadian and Swedish newspapers, respectively. That is, the manner in which news regarding childhood obesity was presented tended to identify individual-level (e.g., increased consumption of junk food, decreased physical activity) behavior and concerns (e.g., women's desire to be physically attractive to men) as germane, discouraging societal-level action to address the problem.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…This finding contrasts with Iyengar's research, in which episodic framing dominated news coverage of social ills. Roy, Faulkner, and Finlay (2007) and Sandberg (2007) identified similar framing patterns in Canadian and Swedish newspapers, respectively. That is, the manner in which news regarding childhood obesity was presented tended to identify individual-level (e.g., increased consumption of junk food, decreased physical activity) behavior and concerns (e.g., women's desire to be physically attractive to men) as germane, discouraging societal-level action to address the problem.…”
mentioning
confidence: 73%
“…One consistent finding in the extant literature is that the manner in which obesity has been framed encourages the perception that the responsibility for obesity rests with the individual, not with society as a whole (Kim & Willis, 2007;Lawrence, 2004;Roy, Faulkner, & Finlay, 2007). Clearly, this perception may lead to significant consequences for public policy, as well as for individual action.…”
mentioning
confidence: 93%
“…From this sample, we identified 14 distinct metathemes and 49 subthemes ( Table 3) that could be further organized into four taxonomic categories (Table 4). An important result of the metasynthesis showed that this sample of qualitative research intensely focused on story construction elements, despite arguments calling for a shift from assessing only content production (e.g., text; see Roy et al, 2007) to more widely understanding health and science journalism through the perspective of journalists. Here it was sourcing practices that played a particularly dominant role in the identified studies.…”
Section: Comparing the Metasynthesis With The Wider Literaturementioning
confidence: 99%
“…Some studies have examined media reporting on obesity from other angles. Roy et al (2007) have explored the ‘interdependent and possibly problematic’ (p. 575) relationships between Canadian journalists and sources that influence how the media cover research on obesity.…”
Section: Introductionmentioning
confidence: 99%